Kemampuan Pemecahan Masalah Siswa SMA dalam Menyelesaikan Soal Usaha dan Energi - Aras Hanif Afiat; Supriyono Koes Handayanto; Hari Wisodo (Jurnal Pendidikan: Teori, Penelitian, dan Pengembangan, 2020)
Abstract: This study aims to determine the problem solving abilities of high school students in solving physics problem topic working and energy. A total of 64 respondents solved physics problem about work and energy which consisted of four questions. The students' answers were evaluated using a rubric consisting of five indicators, namely useful description (UD), physics approach (PA), specific application of physics (SPA), mathematical procedures (MP), and logical progression (LP). The data analysis technique used qualitative descriptive. The results of the analysis show that the score of students' problem solving abilities is in a sufficient category, with the dominant score on indicators UD, PA and SPA. Students get poor score criteria on MP and LP indicators. In this case, students experience some difficulties, among others, students' mistakes in applying physics concepts in mathematical equations, students' mistakes in using equations that are not relevant to the problems presented and students' mistakes in using calculations that do not focus on the problem presented.Abstrak: Penelitian ini bertujuan untuk mengetahui kemampuan pemecahan masalah siswa SMA dalam memecahkan persoalan usaha dan energi. Sejumlah 64 responden mengerjakan soal usaha dan energi yang terdiri atas empat soal uraian. Hasil jawaban siswa dikoreksi dengan menggunakan rubrik yang terdiri atas lima indikator, yaitu usefull description (UD), physics approach (PA), spesific application of physics (SPA), mathematical procedures (MP), dan logical progression (LP). Teknik analisis data menggunakan deskriptif kualitatif. Hasil analisis menunjukkan bahwa skor kemampuan pemecahan masalah siswa berada dalam kategori cukup, dengan dominan skor pada indikator UD, PA dan SPA. Siswa mengalami kriteria kurang baik pada indikator MP dan LP. Dalam hal ini, siswa mengalami beberapa kesulitan, antara lain, kesalahan dalam mengaplikasikan konsep dalam persamaan matematis, menggunakan persamaan yang tidak relevan dengan permasalahan yang dipaparkan menggunakan perhitungan yang tidak fokus pada problem yang disajikan.